Teachers Between Job Satisfaction and Burnout Syndrome: What Makes Difference in Czech Elementary Schools - Smetackova, Irena; Viktorova, Ida; Pavlas Martanova, Veronika; Pachova, Anna; Francova, Veronika; Stech, Stanislav (Frontiers in Psychology, 2019)
As has been shown by several studies, teaching is a highly stressful occupation (Johnson et al. 2005). Most teachers experience work stress. Long-term stress decreases job satisfaction and can result in chronic exhaustion which can develop into burnout syndrome. Implications of burnout syndrome are strongly negative both for the personal and professional life of teachers. As burnout syndrome puts teachers’ well-being, quality of the teaching process and relationships with students at risk, it is important to seek ways to avoid teachersֹ’ burnout. Many studies have confirmed the protective role coping strategies play in managing stressful situations, teacher’s self-efficacy or social support. In previous studies, a negative connection was found between burnout syndrome and job satisfaction. Job satisfaction is a crucial element in the definition of wellbeing. We find wellbeing rather not as resources for burnout prevention but as an opposite state to burnout syndrome. The paper presents a quantitative survey on burnout syndrome and related variables among Czech elementary school teachers (n=2,394). According to burnout score, two subgroups were selected – teachers with no burnout manifestations and teachers with developing/developed burnout syndrome. Through the statistical analysis, these two groups were compared in job satisfaction, self-efficacy, coping strategies, and social support. The study shows the significant differences between the two groups of teachers in all examined variables. The strongest impact on burnout syndrome was found for negative coping.